Dynamic Construction Site Layout Planning Optimization using Genetic Algorithms - درويش رهف; فايز جراد (Latakia University Journal -Engineering Sciences Series, 2023)
Construction site layout planning is one of the basic planning tasks in engineering projects as it plays a major role in reducing project costs, and enhancing productivity and occupational safety on construction sites. Due to the complex nature of construction projects and the multiple factors involved in site layout planning, it was necessary to develop a framework capable of overcoming some of the shortcomings of existing site layout planning models and obtaining more efficient solutions in terms of meeting the physical and qualitative requirements for planning. This research aims to develop a mathematical model for optimizing the multi-objective dynamic construction site layout planning using one of the approximate optimization techniques, which is genetic algorithms in order to generate optimum planning solutions during the construction phases of the project that achieves the various planning objectives of reducing costs and maximizing productivity and safety. The site layout planning problem has been formulated in the form of a mathematical model, and then implement this model as a multi-objective genetic algorithm applied in MATLAB environment. The results of testing the proposed site layout planning model on the case study, proved the efficiency of this model and its ability to generate optimum site planning solutions according to the imposed planning objectives and constraints.